A colorectal cell line with alterations in E-cadherin and epithelial biology may be an in vitro model of colitis. Issue 4 (1st August 1999) - Perry, I; Hardy, R; Jones, T; Jankowski, J
Abstract : BACKGROUND: It has been shown previously in ulcerative colitis tissue that E-cadherin can occasionally be mutated in the extracellular domain early in neoplastic progression. E-cadherin is known to maintain differentiation and inhibits invasion in vivo. AIMS: To assess the mechanisms by which such dysfunction occurs. METHODS: Four human colorectal cancer cell lines, HCA-7 colonies 1, 3, 6, and 30, derived from a single heterogeneous colorectal cancer were studied. The HCA-7 cell line has p53 mutations and a random errors of replication "positive" phenotype, as is seen in early colitis associated cancers or hereditary nonpolyposis coli cancer (HNPCC). RESULTS: Cell lines 6 and 30 expressed E-cadherin abundantly and this correlated positively with their degree of differentiation and organisation; however, both cell lines had loss of heterozygosity of E-cadherin. Interestingly, E-cadherin production was downregulated in the poorly differentiated cell line 1, and this was associated with major chromosomal rearrangements of 16q. This cell line also had a mutation in the homophilic binding domain of exon 4, which was associated with disaggregation by low titres of a function blocking antibody, and an invasive phenotype. CONCLUSIONS: These multiple biological alterations further characterise the complex association that E-cadherin has with tumour heterogeneity and suggest that this series of cell lines may be a useful model of colitis associated or HNPCC associated tumorigenesis.